Research progress in effect of element doping on electrochemical properties of Sr2Fe1.5Mo0.5O6-δ based anode materials - ZHANG Shao-wei; PU Xiu-hao; WAN Yan-hong; ZHU Kang; XIA Chang-rong (Cailiao gongcheng, 2021)
Solid oxide fuel cell (SOFC) is a clean and efficient energy conversion device that can directly convert chemical energy to electricity.The state-of-the-art cermet anodes face various issues such as carbon deposition,sulfur poisoning and poor redox stabilities,which limit the application of SOFC. In order to avoid the problems of the cermet anodes,the perovskite anode materials with mixed electronic-ionic conductivities have drawn considerable attention in recent years.Among them,Sr2Fe1.5Mo0.5O6-δ perovskite has good stability,high conductivity,suitable thermal expansion coefficient and excellent electrochemical performance,and thus has been widely studied,especially element doping.The element doping was discussed at A-site,B-site and O-site of Sr2Fe1.5Mo0.5O6-δ perovskite,and the effects of doping elements and doping content on crystal structure,stability,electronic conductivity,thermal expansion and electrochemical performance were summarized.These doping strategies provide some novel ideas for modifying Sr2Fe1.5Mo0.5O6-δ perovskite anode,which can also be used to modify other similar perovskite anode materials.Finally, the development direction of Sr2Fe1.5Mo0.5O6-δ and typical ceramic anode materials was prospected. On one hand, the strategies of anion doping and co-doping could be adopted to improve the performance of ceramic anode materials. On the other hand,the mechanism of element doping will be further clarified through the combination of doping strategy and theoretical calculation.